Development of Student Worksheets Using The Missouri Mathematics Model with Peer Feedback on Linear Programming Material - Naimnule, Maria; Kehi, Yohanes Jefrianus; Handayani, Rika (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aimed to develop a valid, practical, and effective student worksheet (LKS) for linear programming material based on the Missouri Mathematics Project (MMP) model with peer feedback. Using a Research and Development (R&D) design comprising definition, design, development, and dissemination stages, data were collected through validation sheets, questionnaires, and tests. The developed worksheet was assessed as valid by experts 80%, practical based on student and teacher responses 85%, and effective in improving learning outcomes. Effectiveness was indicated by 79% classical completeness and a significant improvement in Post test scores compared to Pre test results (p < 0.05 ). The findings show that the MMP-based worksheet with peer feedback meets the criteria for valid, practical, and effective learning tools.